The study of land management and geographic information support of municipal building in Ukraine - Nesterenko, Sergey; Vyatkin, Konstantin (Technology audit and production reserves, 2017)
The urgent problems and methods of land management and geoinformation support of the municipal building branch for the development of Ukrainian settlements according to the cities of leading European countries are considered in the article. The methodology of keeping and control of municipal building cadastre under the modern conditions at regional, state and world levels is elaborated. The approaches to land management and creation of municipal building cadastre and main principles of the work in cadastre system of Ukrainian cities were systematized and generalized; the possibilities of the solution of practical tasks as to information systems in general geoinformation system of municipal building cadastre were established. It was established, that the specificity of information system that provides the municipal building decisions is not only in data structure but in the necessity to involve the retrospective and forecasting data along with actualized ones that is a function of municipal building data bank.